FRACTALS IN GEOLOGY, GEOTECTONIC AND GEODYNAMIC ASPECTS - V. M. Kharchenko; D. V. Lapta (Наука. Инновации. Технологии)
Introduction: the paper deals with the general concepts of fractals, their geodynamic and geotectonic aspects. An example is given of the most obvious fractals - structures of the central type, in particular, stretching structures. As a result of their interpretation, a connection with minerals), ecological conditions and seismicity of the territories of the global, regional and local plans is shown. Materials and research methods: The theoretical basis of these studies is: the rotational concept of tectogenesis [7], the fuid-dynamic theory of B.A.Sokolov [6], the concept of tectonic stress felds and earthquakes by M.V. Gzovsky [3], the theory of "geosolitons" by R.M. Bembel [1] and the concept of the nature of structures of the central type by V.M. Kharchenko [7, 8]. The main methods of scientifc research were used: 1. Remote - systemaerospace; 2. The method of similarities and analogies; 3. Structural and metric; 4. Landscape-indication; 5.Axiomatic. Research results and their discussion: to confrm the relationship of fractals with minerals, seismicity and environmental conditions, the author deciphered space images, topographic maps, physical geographic maps and even a globe with the allocation of fractals (SCT) of various ranks with their subsequent interpretation and overlaying maps of minerals known anomalous phenomena (such as the Bermuda Triangle, the Tunguska event, etc.). As a result, in some cases, astounding information was obtained that makes it possible to explain the known phenomena (places of formation of tornadoes and typhoons, falling meteorites, the origin of oil swamps and lakes, the place of origin of earthquakes and volcanoplutonic activity, migration routes of harmful pollutants on the earth's surface and in the upper layers of the earth's crust. etc.). Thus, within the known Astrakhan gas condensate feld, fractal analysis reveals the migration paths of pollutants (radionuclides) through the zones of interference of the discharge areas and areas of their possible accumulation in the foodplain and delta of the Volga River. Such examples can be cited in any territory of Russia and other countries. Conclusions: as a result of the conducted studies, it was revealed that SCTs are a clear example of geological fractals, the interpretation of which proved the possibility of searching for mineral deposits, including oil and gas, predicting natural anomalous phenomena, environmental conditions and seismicity of territories of different scales.